Evidence for a heavily glaciated Antarctica during the late Oligocene "warming" (27.8–24.5 Ma): Stable isotope records from ODP Site 690. (20th April 2017) - Hauptvogel, D. W.; Pekar, S. F.; Pincay, V.
Abstract: High δ 18 O values (> 3.0‰) from a 9 kyr resolution benthic foraminiferal stable isotope record from the Ocean Drilling Program hole 690B located on the Maud Rise, Antarctica, indicate a heavily glaciated Antarctic continent during late Oligocene (27.8–24.5 Ma). Values ranging 2.5–3.0‰ during interglacial periods and 3.0–3.6‰ during glacial intervals are consistent with an ice sheet near or larger than modern size. In addition, this record does not exhibit the long‐term late Oligocene warming trend seen in records from low‐latitude drill sites. Oxygen isotope values from 26.0 to 24.5 Ma are comparable (ranging between 2.5 and 3.3‰) to values that preceded the δ 18 O event Oi2b at 26.7 Ma, indicating no significant glacial collapse occurred during the late Oligocene. A gradient between ocean basins during the Oligocene has already been linked to the development of a modern, multilayered ocean and worked to bathe the low latitude to midlatitude, deep‐sea records with a warmer water mass. We suggest that this masked the significant Antarctic glaciation in low‐latitude paleoceanographic records. Additionally, we propose a resolution for conflicting lines of evidence from some Antarctic proximal records suggesting significant glaciation and others suggesting reduced glaciation during the late Oligocene by allowing a modern‐sized ice sheet to grow on an Antarctic continent as more land surface area existed above sea level during this time. This could allow at least some portions of the Antarctic coastline to remain ice‐free during glacial minima while still maintaining modern or near‐modern ice volume. Key Points: Antarctic proximal oxygen isotope record reflects a large ice sheet during the late Oligocene Significant amount of ice in West Antarctica during the late Oligocene Low‐latitude isotope records influenced by a water mass that is masking Antarctic glaciation